JUAL BELI BUKET UANG MENURUT PANDANGAN WAHBAH AZ-ZUHAILI - ahmad, sifak saifuddin; Mufatzizah, Maranda Sukma; Balqis, Malikah (Hukum Islam, 2023)
This study discusses the views of Islamic law related to buying and selling bouquets of money from the perspective of Wahbah az-Zuhailiy. Money that was originally only used as a medium of exchange, with the development of human creativity, money can also be used as a series of beautiful arts in the form of a bouquet. Viewed from the other side, it is stated that it is not allowed to sell or exchange money for money with suspension and excess. This research is a library research that in its approach uses an analytical descriptive approach, by knowing the description and practice of buying and selling bouquets of money in the field. According to Wahbah Az-Zuhaili, buying and selling a bouquet of money includes buying and selling currency with currency that contains additional accessories. Thus, it can be concluded that in buying and selling a bouquet of money, the contract in buying and selling is not purely buying and selling currency with currency only, but rather buying and selling currency with currency with other accessories added, so that the law is valid according to one opinion and invalid according to another. This paper is expected to help answer the law of buying and selling a bouquet of money, especially for every party involved in this money bouquet business.